SOCIAL COMPUTING: AN INTELLIGENT AND RESPONSIVE SYSTEM - Dev Rishi Tekriwal; Arkaprava De; D, Ezhilmaran (European Scientific Journal, ESJ, 2013)
This paper deals with the advantages of a graphical database over conventional database in terms of real world applications. The unique property exhibited by the graphical databases which is, that the edges inside the graph which is the relationship between the nodes can be dynamically changed in real time without any computational overrides thereby providing a more optimized structure to compute and manipulate, is given as a hypothesis in this paper. It also throws light on how the data mining techniques can be implemented in the social networking, thus making it more intelligent and responsive systém. It also propose a methodology to generate a social graph of user’s action and predict future social activities using graph mining. Through this model, we believe that it becomes clearer that data from different contexts can be related such that new solutions can be explored and thus, it may provide illumination for the aforementioned problems and stimulate new research.